Does Size Matter? The Productivity of Government: Expenditures and the Size of States: Evidence from India - Cornelis W. Haasnoot (German Institute of Global and Area Studies (GIGA), 2016)
Some politicians argue for the splitting and combining of states to increase government productivity, but there is a dearth of empirical evidence on the optimal size of a state. Using data from Indian states, I test a model of the optimal size of the state. I find that size and preference heterogeneity do not significantly affect the productivity of a state government. However, when states are split up, the productivity of the root state's government is negatively affected. This suggests that there may be a readjustment phase after state reorganisation that brings about this negative effect. It is important to consider this effect when redrawing state borders.
Keywords: H11; H40; H50; H72; H77; 330; India; fiscal federalism; government quality; ethnic heterogeneity; state reorganization